2021
DOI: 10.3390/ijms22041822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Western Diets on Non-Alcoholic Fatty Liver of Male Mice Modifying the PPAR-γ Pathway via miR-27b-5p Regulation

Abstract: Western diets contribute to metabolic diseases. However, the effects of various diets and epigenetic mechanisms are mostly unknown. Here, six week-old C57BL/6J male and female mice were fed with a low-fat diet (LFD), high-fat diet (HFD), and high-fat high-fructose diet (HFD-HF) for 20 weeks. We determined that HFD-HF or HFD mice experienced significant metabolic dysregulation compared to the LFD. HFD-HF and HFD-fed male mice showed significantly increased body weight, liver size, and fasting glucose levels wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
4
18
0
Order By: Relevance
“…However, it has been shown that SREBP gene expression may be altered depending on feeding or fasting state, where fasting decreases SREBP-1c levels [ 36 ], which may explain the lack of alteration in the liver of these animals. Similarly, while most reports show an increase in SCD1 expression under NAFLD conditions, a decrease has also been observed [ 37 ]. In this work, we did not show SIRT2 interaction with SREBP-1c; however, it has been shown that SIRT2 regulates SREBP-2 of the same family.…”
Section: Discussionmentioning
confidence: 79%
“…However, it has been shown that SREBP gene expression may be altered depending on feeding or fasting state, where fasting decreases SREBP-1c levels [ 36 ], which may explain the lack of alteration in the liver of these animals. Similarly, while most reports show an increase in SCD1 expression under NAFLD conditions, a decrease has also been observed [ 37 ]. In this work, we did not show SIRT2 interaction with SREBP-1c; however, it has been shown that SIRT2 regulates SREBP-2 of the same family.…”
Section: Discussionmentioning
confidence: 79%
“…Overall, these results were similar to our previous studies and others utilizing a diet-induced mouse model of MetS [ 11 13 ]. Previously, we demonstrated that the MetS mouse model also exhibits elevated plasma insulin level [ 12 ] while others have reported elevated blood glucose [ 30 , 31 ] and hypertension [ 32 ]. AgNP exposure and/or treatment with RvD1 did not alter body weight or serum levels of TC, HDL, LDL, and TG in either healthy or MetS mouse models (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This HFW diet is well established to generate mouse models of MetS and has been used by our group and others for studies evaluating MetS [ 11 13 , 78 ]. Specifically, other studies have demonstrated mice on this diet exhibit key factors of MetS such as obesity, elevated cholesterol, increased glucose, increased glucose tolerance, and hypertension [ 11 13 , 30 , 31 , 75 ]. Males were included to allow for comparisons to previous studies establishing dysregulation of SPMs 24 h following AgNP exposure.…”
Section: Methodsmentioning
confidence: 99%
“…have reported the correlation between western diets and the expression of miR-27a-5p. They reported that the up regulated miR-27a-5p induces fatty liver disease by suppressing the expression of PPARγ [ 34 ]. Another study also reported that down regulation of miR-27a-5p might be able to abolish hypoxia-induced cardiomyocyte injury through targeting apoptotic and autophagy-related pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%